Development of Physics Digital Props Based on the Internet of Things (IoT) on the Material of Motion Dynamics - Wahyudi, Muh.; Azmar, Azmar; Muhayadi, Samsul; Firmansyah, Muhammad Arif (Jurnal Pendidikan Fisika, 2024)
This research aims to create an Internet of Things (IoT)-based Newton's Law II physics practicum trainer. The developed props aim to make the students understand measure time, speed, and acceleration in Particle Dynamics Using IoT-based teaching aids. The design of teaching aids uses electronic components such as ESP32 WIFI-Bluetooth microcontrollers, obstacle Infrared Sensors, and LCDs as the main hardware components. The software for developing this teaching aid utilizes the Arduino IDE compiler based on C++. The development research method used is the ADDIE design development method. The ADDIE design development stages include Analyze, Development, Implementation, and Evaluation. The product feasibility test involved 35 SMAN 1 Montong Gading students. Expert validators in the media and material carry out the feasibility test. The feasibility test results in the media and material sector are 95%, with a very feasible category. The scores of the student's responses to the development are 77% with a practical. The results showed that the physics teaching aids developed were very valid and feasible to use.